Copy number variation in the ATP‐binding cassette transporter ABCC6 gene and ABCC6 pseudogenes in patients with pseudoxanthoma elasticum. Issue 3 (8th March 2015) - Kringen, Marianne K.; Stormo, Camilla; Berg, Jens Petter; Terry, Sharon F.; Vocke, Christine M.; Rizvi, Samar; Hendig, Doris; Piehler, Armin P.
<x xml:space="preserve">Abstract</x> In this study, principally by pyrosequencing, we were able to detect known and possibly new deletions in the ABCC6 gene that may have caused pseudoxanthoma elasticum (PXE). Also, duplication of the ABCC6P2 pseudogene was common in PXE patients which may possibly affect the PXE phenotype.